Necking in extrusion film casting: numerical predictions of the maxwell model and comparison with experiments - Pol, Harshawardhan V.; Thete, Sumeet S. (Journal of Macromolecular Science Part B-Physics, 2016)
The role of viscoelasticity in determining the extent of necking of a web of molten polymer extruded in an isothermal steady state extrusion film casting (EFC) process is considered. Following a brief review of experimental and theoretical efforts on this problem, analytical and numerical solutions to a well-established model for extrusion film casting using the Maxwell constitutive equation is presented. The extent of film necking was found to either increase or decrease with draw ratio (DR) depending on the Deborah number (De). The locus of points on the draw ratio-Deborah number diagram at which the draw ratio dependence of the necking width inverts was calculated and compared with the locus that separates the unattainable regime from the experimentally accessible regime. Predicted trends were found to be in qualitative agreement with experimental data for various polyethylene grades.